A descriptive study of an adult non- trauma emergency centre at a Cape Town central referral hospital - Kubeka, Vuyiswa (Department of Public Health and Family Medicine, 2024)
Objective: The study evaluated the demographics and acuity of patients at a South African central referral hospital. The triage acuity, diagnosis and disposition from the Emergency Centre (EC) were assessed, and the impact of COVID19 initial lockdown on presentations as a secondary outcome. Methods: Data were collected retrospectively from 1 March 2019 to 31 May 2020, including the first 2-month COVID 19 lockdown period. Data was entered electronically by EC staff for routine healthcare management processes, including final ICD 10 code diagnosis on leaving the EC. Results: A total of 38477 patients were included, 20 excluded, with a mean of 2565 seen per month prior to the COVID lockdown when there were 1619 monthly. Lower acuity patients were largely either referred by a general practitioner or self-referred. Of the discharged patients,64% were lower acuity. Some 57% of specialist referrals were high acuity. The top four disease categories were cardiovascular 15%, gastrointestinal and hepatobiliary 14%, neurology 13 % and respiratory 12%. Disposition for referral to an inpatient specialist was 42%. Patients discharged from the EC amounted to 35%. Total time in the EC for patients referred to an inpatient specialist were a median of 561 minutes and 23 minutes for discharged patients. Conclusion: Central referral hospitals offer specialty and subspecialty services for emergency and outpatient presentations. A good deal of the patient load on the EC was relatively low acuity patients that might be more efficiently seen elsewhere such as subspecialty outpatient clinics to alleviate the burden on the EC, and to free it up for high acuity patients. This study can serve as a foundation for reflection on the use of a specialised central referral hospital EC as a resource in the healthcare system. We observed a global trend of decreased EC presentations during COVID19 lockdown period.